THE STRUGGLE OF FORD WOMEN WORKERS AGAINST STEREOTYPE AS DEPICTED IN MADE IN DAGENHAM THE MOVIE - ANDARI EKA, DIONISIA WIDYARAGA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Equality, rights and women position are what women desire. The position of women at their era made women who are called feminist initiate a movement to gain equal rights with men. The movie entitled Made in Dagenham revealed the struggles of the women who worked at Ford, a car factory in the town of Dagenham, against the stereotypes attached to women to get equal pay with men. This research uses a feminism approach that focuses on Marxist feminism. This study also uses the concept of stereotypes, prejudice, and discrimination. The result of the study reveals women are treated unfairly in a society that has been established to prioritize men. The movie Made in Dagenham showed one example of injustice faced by the women of the working class. They obtain a lower salary than male workers. Rita O'Gardy, the main character in this movie leads the movement that aim to get equal pay for women and break the stereotype that women are unskilled labors.     Key words: Stereotype, women, men, equality, salary.